MODERN WAYS OF DEVELOPING PILGRIMAGE TOURISM IN UZBEKISTAN (World Bulletin of Management and Law, 2023)
In modern development, the development of tourism has its place. Today, large-scale reforms are carried out in Uzbekistan in all spheres of social life, and the main goal of these reforms is an indicator of the further development of the country's economy and the improvement of the living well-being of the Uzbek people. Tourism plays an important role in the economic development and growth of Uzbekistan, and in the following years, great attention is paid to the development of pilgrimage tourism in the country, among other areas of Tourism.